Keterbukaan Diri Pria yang Telah Menikah - Anggia Wahyu Agustin; Berru Amalianita; Ifdil Ifdil (SCHOULID: Indonesian Journal of School Counseling, 2018)
This study describing the self disclosure husband in young married couple. Type of the research is quantitative descriptive. Research subjects are young age couples who totaled 42 men. Instruments used for data collection is a likert model scale. Dana analyzed is using percentage and interval. The results of this reseach is self disclosure husband in the open category.Based on finding of research, hopefully the counselor can provide professional assistance with information services and personal counseling to help young couple to enhancing self dislcosure.